Mark Orsag email to Thomas Kent regarding Hitchcock Nature Area Hawkwatch, December 20, 1999 - Orsag, Market al (1999)
Printout of an email from Mark Orsag to Thomas Kent dated December 20, 1999. Orsag sends Kent a raptor count and mentions other bird sighting reports he has sent in. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed